2013
DOI: 10.4103/2006-8808.128723
|View full text |Cite
|
Sign up to set email alerts
|

Facial fracture management in Northwest Nigeria

Abstract: Background:Facial fracture is gradually become a public health problem in our community due to the attendant morbidity and mortality. Hence, the aim of this study was to determine the pattern of facial fracture in Dental and Maxillofacial Surgery Department of Usmanu Danfodiyo University Teaching Hospital. This cross-sectional study was undertaken to provide information regarding gender, age, etiology, and diagnosis of patients with maxillofacial fractures.Materials and Methods:A 1-year review of patients diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
5
11
0
Order By: Relevance
“…Mandibular fractures were more commonly encountered than any other maxillofacial fracture. This finding is comparable to other reports in the literature [ 3 , 14 , 25 ]. However, it is at variance with some other studies where nasal bone fractures were reported to be the most frequently encountered maxillofacial fracture [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mandibular fractures were more commonly encountered than any other maxillofacial fracture. This finding is comparable to other reports in the literature [ 3 , 14 , 25 ]. However, it is at variance with some other studies where nasal bone fractures were reported to be the most frequently encountered maxillofacial fracture [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Despite the availability of the necessary armamentarium and requisite expertise, patients often opted for closed reduction. Possible reasons for the adoption of closed reduction as reported by various authors range from financial incapacitation on the patients’ part to fear of general anesthesia [ 14 , 25 , 30 ]. Most patients in our climes make out-of-pocket payment for their treatments and this is often challenging [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study result is in agreement with findings reported by Igho et al, Taiwo et al, Kadkhodaie; Khanbhai and Lutomia, which observed the male gender had a higher predilection to this medical condition than the females [15,19,8,6]. These results could be the high predominance of males involved in manual activities (construction, driving of vehicles, motorcycle riding etc.)…”
Section: Resultssupporting
confidence: 93%
“…This could be explained by the tendency of riders and passengers of these "Okadas" to be males. This observation is similar to a study in Nigeria [5]. with the "Aboboyaa" motor tricycles.…”
Section: Discussionsupporting
confidence: 91%
“…Head and facial fractures are among the frequently affected parts of the body during road traffic accidents [1] to the extent that it has been reported that 20% -60% of all individuals involved in automobile accidents have some level of facial fractures [2] [3]. The face, being the most exposed part of the body, is particularly vulnerable to such injuries including injuries of victims of motorcycle accidents [3] [4] [5].…”
Section: Introductionmentioning
confidence: 99%